2003
DOI: 10.1523/jneurosci.23-13-05561.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ErbB2 Signaling in the Onset of Terminal Differentiation of OligodendrocytesIn Vivo

Abstract: The knock-out analyses of neuregulin and its receptors have indicated that they play essential roles in Schwann cell development. However, the role they play in oligodendrocyte development in vivo has remained unclear, because such knock-out animals die before CNS myelination begins. We examined the role of neuregulin signaling in the CNS by generating transgenic mice that express a dominant-negative mutant of the ErbB2 receptor among oligodendrocytes, using an MBP promoter. The transgenic mice exhibited wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 61 publications
4
64
3
Order By: Relevance
“…This allowed us to conclude that the cessation of OPC cell division and subsequent terminal OL differentiation is actually a complex, multistep process, which requires several days to reach completion. It has been widely demonstrated that external stimuli from axons and other sources can affect OL survival, differentiation, and myelin sheath formation (Barres et al, 1993(Barres et al, , 1994Barres and Raff, 1999;Stevens et al, 2002;Kim et al, 2003), but to our surprise we found little evidence for an axonal role in controlling OL gene expression. To determine how closely our in vitro study recapitulates normal OL differentiation, we have compared the gene expression profile of our in vitro-generated OLs to that of acutely isolated OLs that have matured in vivo.…”
Section: Ol Differentiation Progresses Fully In the Absence Of Heterocontrasting
confidence: 62%
See 1 more Smart Citation
“…This allowed us to conclude that the cessation of OPC cell division and subsequent terminal OL differentiation is actually a complex, multistep process, which requires several days to reach completion. It has been widely demonstrated that external stimuli from axons and other sources can affect OL survival, differentiation, and myelin sheath formation (Barres et al, 1993(Barres et al, , 1994Barres and Raff, 1999;Stevens et al, 2002;Kim et al, 2003), but to our surprise we found little evidence for an axonal role in controlling OL gene expression. To determine how closely our in vitro study recapitulates normal OL differentiation, we have compared the gene expression profile of our in vitro-generated OLs to that of acutely isolated OLs that have matured in vivo.…”
Section: Ol Differentiation Progresses Fully In the Absence Of Heterocontrasting
confidence: 62%
“…Another interesting finding is the detection of neuroglycan C gene expression, which has been recently characterized as a novel ErbB3/ErbB2 ligand (Kinugasa et al, 2004). This is interesting, because ErbB2 activation enhances OL differentiation and survival (Fernandez et al, 2000;Park et al, 2001;Kim et al, 2003), suggesting the possibility that, in the early stages of OL differentiation, OPC-derived neuroglycan C could provide support for newly forming OLs until they tightly wrap axons, whereupon the axonally expressed ErbB2 ligand neuregulin could then support myelinating OLs (Barres and Raff, 1999).…”
Section: Analysis Of the Genes Most Highly Expressed By Opcsmentioning
confidence: 99%
“…Disruption of NRG1 signaling by DN-ErbB4 or kinase dead ErbB1 impairs oligodendrocyte differentiation in transgenic mice (32,33). However, myelination deficits in the central nervous system (CNS) are relatively minor and limited to frontal brain regions in hypomorphic mutants of type III NRG1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action of trastuzumab are complex and not fully understood. Described mechanisms include receptor downregulation (Sliwkowski et al, 1999;Ozcelik et al, 2002;Diermeier et al, 2005;Yuste et al, 2005), cell cycle arrest (Kim et al, 2003), inhibition of angiogenesis (Izumi et al, 2002) and induction of antibody-dependent cell-mediated cytotoxicity (ADCC) (Clynes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%